The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fphar.2020.569402
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gum Acacia on the Composition of the Gut Microbiome and Plasma Levels of Short-Chain Fatty Acids in a Rat Model of Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) may be fatal for its victims and is an important long-term public health problem. The complicated medical procedures and diet restrictions to which patients with CKD are subjected alter the gut microbiome in an adverse manner, favoring over-accumulation of proteolytic bacteria that produce ammonia and other toxic substances. The present study aimed to investigate the effect of GA on 1) the composition of the gut microbiome and 2) on plasma levels of short-chain fatty acids. Male Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Furthermore, a recent clinical study recruiting 30 patients with DKD confirmed that SCFAs were reduced in serum and stool compared to 30 normal controls [81]. In line with those clinical findings, the decreased plasma levels of SCFAs and impaired renal function were observed in a rat model of CKD induced by dietary adenine, which was attenuated by gum acacia [82]. In a DKD mouse model induced by streptozotocin (STZ), Li et al reported that a high-fibre diet significantly reduced albuminuria, kidney hypertrophy, glomerular injury, tubulointerstitial fibrosis, and interstitial macrophage infiltration compared with healthy controls.…”
Section: Gut Microbial Metabolites and Ckdsupporting
confidence: 59%
“…Furthermore, a recent clinical study recruiting 30 patients with DKD confirmed that SCFAs were reduced in serum and stool compared to 30 normal controls [81]. In line with those clinical findings, the decreased plasma levels of SCFAs and impaired renal function were observed in a rat model of CKD induced by dietary adenine, which was attenuated by gum acacia [82]. In a DKD mouse model induced by streptozotocin (STZ), Li et al reported that a high-fibre diet significantly reduced albuminuria, kidney hypertrophy, glomerular injury, tubulointerstitial fibrosis, and interstitial macrophage infiltration compared with healthy controls.…”
Section: Gut Microbial Metabolites and Ckdsupporting
confidence: 59%
“…According to the classification of dysfunction indicators and inflammation indicators related to acute arthritis symptoms, an acute gouty arthritis model was established. 28 Dysfunction index evaluation was also recorded (Level 0: normal gait, evenly landing on all four feet; Level 1: relaxed left foot, toes spread out, mild lameness; Level 2: left hind foot flexed, toes touching the ground, visible limp; Level 3: Left hind foot completely leaves the ground). After injection of MSU crystals or PBS solution, the dysfunction index of rats was evaluated at 0h, 12h, 24h, and 48h.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing publications have demonstrated that CKD could be ameliorated by improving the dysbiosis of gut microbiota via some intervention strategies [82,83]. Mo and his colleague [84] demonstrated that treatment with α-Ketoacid could decrease the levels of serum creatinine, blood urea nitrogen and 24 h proteinuria, as well as retarded interstitial fibrosis and glomerulosclerosis in the adenine-induced CKD rats.…”
Section: Intervention Strategies Through Regulating Gut Microbiota In...mentioning
confidence: 99%